Processes controlling the behavior of LNAPLs at groundwater surface water interfaces - Hawkins, Alison M., author; Sale, Tom, advisor; Zimbron, Julio, committee member; Ronayne, Michael, committee member (Colorado State University. Libraries, 2013)
Releases of Light Non-Aqueous Phase Liquids (LNAPLs) are a significant problem at many sites. This thesis explored governing processes pertaining to LNAPL releases at groundwater surface water interfaces (GSIs). Governing processes were investigated via laboratory studies and a preliminary analysis of forces controlling LNAPL occurrence in unsaturated media. A total of six laboratory sand tank experiments were conducted using novel applications of fluorescing dyes. The results of these experiments provide unique insights regarding LNAPL behavior in porous media. Key insights include: * LNAPLs occur in three distinct zones, herein referred to as Zone 1, 2, and 3. Zone 1 refers to the area below the water capillary fringe where LNAPL is a discontinuous nonwetting phase. Zone 2 refers to the area below the LNAPL capillary fringe where LNAPL is a continuous nonwetting phase. Zone 3 refers to the area above the LNAPL capillary fringe where LNAPL is a continuous intermediate wetting phase. Each zone has unique attributes controlling LNAPL mobility * Solutions for LNAPL releases at GSIs need to address transport of LNAPL in all three zones * Modeling fluid saturations versus height in a porous media using a force balance is more complex than two forces and requires further research A common theme with current solutions for LNAPLs at GSIs is their failure with time. Failure is defined as the observation of LNAPL down-gradient of the solution. A better understanding of these failures is advanced through a volume balance on a representative elementary volume (REV) of porous media at a GSI. Key factors controlling releases to surface water include inflows, natural losses, enhanced losses, and recovery of LNAPL in the REV. Furthermore, the timing of failure is dependent on the capacity of the REV to store LNAPL prior to releases to surface water. A novel solution demonstrated in this thesis was the use of capillary barriers to limit LNAPL lateral migration. Herein, capillary barriers are defined as vertical walls of fine-grained media that preclude lateral movement of LNAPL via a capillary pressure less than the displacement pressure in Zone 2 and an elevated water capillary fringe in Zone 3. A capillary barrier alone can delay releases; however, the barrier will fail when LNAPL storage capacities are exceeded. In contrast, the use of a recovery well to deplete accumulating LNAPL, in combination with a capillary barrier, provides a sustainable solution. During a laboratory experiment, 92% of the delivered LNAPL held behind the capillary barrier was recovered by aggressively pumping at low water stages. A second strategy explored to control LNAPL releases at GSIs was organoclay barriers. Herein, organoclay barriers are defined as vertical walls of organoclay-sand mixtures. Organoclay is hydrophobic and retains LNAPL via sorption. Using a "simple" organoclay barrier, breakthrough to surface water was observed when only 11% of the organoclay was saturated with LNAPL. Early failure was attributed to preferential pathways and slow water drainage. Adding vertical baffles and vertical coarse-grained drains improved the efficacy of organoclay barriers. Fractions of the clay contacted at breakthrough were 43% and 34%, respectively, for baffles and drains. A concern that arose from the sand tank studies was the necessary water capillary rise in the capillary barrier to preclude LNAPL migration in Zone 3. This led to an attempt to develop a force-based model describing LNAPL (intermediate wetting phase) saturations in Zone 3. The model would be beneficial to determine the vertical rise of LNAPL at sites with non-tidal conditions. Key factors included in the model include spreading coefficients and gravity. The model developed (Model 1) was compared to three-phase data. It was found that Model 1 had poor correlation to the data and lacked some key factor affecting saturations. The model was altered by raising Model 1 to the power of lambda and adding the residual saturation, resulting in Model 2. Model 2 was compared to two-phase data and the Brooks-Corey equation and showed promising similarities. The work described in this thesis provides a basis for future work on remediation solutions and mathematical models for LNAPLs at GSIs. Work could include development of strategies to enhance natural losses of LNAPLs at GSIs and further refinements to Model 1 and Model 2 to better capture factors controlling fluid saturations in Zone 3.
Keywords: migration; groundwater surface water interfaces; LNAPL; intermediate wetting phase